1999
DOI: 10.1016/s0092-8674(00)81549-4
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Vinculin Tail Suggests a Pathway for Activation

Abstract: Vinculin plays a dynamic role in the assembly of the actin cytoskeleton. A strong interaction between its head and tail domains that regulates binding to other cytoskeletal components is disrupted by acidic phospholipids. Here, we present the crystal structure of the vinculin tail, residues 879-1066. Five amphipathic helices form an antiparallel bundle that resembles exchangeable apolipoproteins. A C-terminal arm wraps across the base of the bundle and emerges as a hydrophobic hairpin surrounded by a collar of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
243
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(268 citation statements)
references
References 58 publications
19
243
0
2
Order By: Relevance
“…Furthermore, it has been suggested that talin acts downstream of vinculin in this signaling pathway, where the binding of PI(4,5)P 2 to the Vt domain of vinculin has been proposed to "unfurl" its five-helical bundle, thus severing its intramolecular interaction with Vh and allowing Vh then to bind to talin and other partners (25,31). Our structures of the Vh⅐VBS1 and Vh⅐VBS3 complexes, the validated model of the Vh⅐VBS2 complex, and the ability of all three VBSs to displace Vt from preexisting Vh⅐Vt complexes now suggest a different model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been suggested that talin acts downstream of vinculin in this signaling pathway, where the binding of PI(4,5)P 2 to the Vt domain of vinculin has been proposed to "unfurl" its five-helical bundle, thus severing its intramolecular interaction with Vh and allowing Vh then to bind to talin and other partners (25,31). Our structures of the Vh⅐VBS1 and Vh⅐VBS3 complexes, the validated model of the Vh⅐VBS2 complex, and the ability of all three VBSs to displace Vt from preexisting Vh⅐Vt complexes now suggest a different model.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional model has suggested that these constraints are simply relieved by the binding of PI(4,5)P 2 to the Vt domain (25), which can insert into acidic phospholipid bilayers (30). Indeed, binding of PI(4,5)P 2 changes the conformation of Vt, and this facilitates the in vitro interaction of Vt with F-actin (31) and, by disrupting the Vh-Vt interaction, has been suggested to allow talin binding to Vh (25,31). However, other models are now equally plausible because talin VBS3 and the vinculin binding site of ␣-actinin can displace Vt from preexisting Vh⅐Vt complexes (32).…”
mentioning
confidence: 99%
“…The crystal structures of the vinculin tail and the FAK FAT domain, which contain the PBS, have been solved (7,10,91,114). FAK FAT solution structures have also been reported (66, 152).…”
Section: A Paxillin Ld Motifsmentioning
confidence: 99%
“…The vinculin tail and FAK FAT domain share a parallel up-down-up-down four-helix bundle. This general structural organization is shared by ␣-catenin, apolipoprotein E, and the p130Cas family of proteins (7,10,91,114), although only vinculin and FAK bind paxillin. Interestingly, structural predictions suggest that the PBS-FIG.…”
Section: A Paxillin Ld Motifsmentioning
confidence: 99%
See 1 more Smart Citation